2014
DOI: 10.1152/ajpheart.00038.2014
|View full text |Cite
|
Sign up to set email alerts
|

An optimized method for estimating the tidal volume from intracardiac or body surface electrocardiographic signals: implications for estimating minute ventilation

Abstract: The ability to accurately monitor tidal volume (TV) from electrocardiographic (ECG) signals holds significant promise for improving diagnosis treatment across a variety of clinical settings. The objective of this study was to develop a novel method for estimating the TV from ECG signals. In 10 mechanically ventilated swine, we collected intracardiac electrograms from catheters in the coronary sinus (CS), left ventricle (LV), and right ventricle (RV), as well as body surface electrograms, while TV was varied be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 31 publications
0
30
1
Order By: Relevance
“…Thereafter, we used previously developed algorithms for the estimation of the RR23, TV22 and ischemic index21, which were modified for the cvrPhone described above, and for which we first confirmed that their JAVA implementation for the Android was equivalent to the previously developed one in MATLAB (see Supplement, Figures S5–7). …”
Section: Resultsmentioning
confidence: 86%
“…Thereafter, we used previously developed algorithms for the estimation of the RR23, TV22 and ischemic index21, which were modified for the cvrPhone described above, and for which we first confirmed that their JAVA implementation for the Android was equivalent to the previously developed one in MATLAB (see Supplement, Figures S5–7). …”
Section: Resultsmentioning
confidence: 86%
“…Here, we have extended this concept to a very non-stationary situation, such as a maximum effort treadmill test, where TV is constantly varying. Lowest relative errors obtained in [9] were comprised between 7 and 10%. With the proposed method, we achieved relative errors around 7% in the best-performing lead and stage.…”
Section: Discussionmentioning
confidence: 93%
“…A previous step to this work was proposed in [9], although this study presented some limitations. First, mechanical controlled ventilation is a very invasive procedure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…11 Recently, Weiss et al, used an algorithm that selected the best leads to derive respiratory rate from either intracardiac or body surface ECG in intubated and mechanically ventilated swine; 12 furthermore, modulation in the ECG derived respiratory rate was used by the same group to derive tidal volume. 13 Alternatively, ECG data routinely collected during polysomnography has been used to derive apnea and hypopnea; 1416 using cyclic variations of the heart rate 14 , or changes in the QRS complex, 1516 and with an accuracy to detect the events of 89%, 84% and 85% respectively. 1416 …”
mentioning
confidence: 99%